The soft bottom macrozoobenth05 in front of Catarindo bay during "El Niño 1997-98" - Coayla, Pastor (1999)
The changes in macrozoobenthos were analyzed during January of 1997 lo July 01 1998 in Catarindo station (Mollendo-Arequipa) located at 17°01'13" LS and 72°02'19" LW. The samples were analyzed with a van Veen dredge 01 0,04 m2 to 34 m depth. A total of 50 different species, correspond to polychaete, mollusks, crustacean and others, were recorded; there were an increase of mollusks and crustacean species in 1998 which were absent in 1997. During "El Niño 1997-98" polychaete towered over numerically, being the most important species Prionospío peruana, Nephtys multícirrata, Goniada sp. and Leitoscoloplos chilensis. The major macrozoobenthos density was recorded in spring of 1997, and part of summer 1998, corresponding to P. peruana. The biomass fluctuated and the highest value corresponded to the polychaete group in 1997, but in 1998, the biomass increase corresponded to mollusk group. The diversity presented values ranged between 1,5 and 3,2 bits, the highest values were recorded during summer and winter of 1997 and at the end of summer and beginning of autumn 1998.